Precipitation-based grain boundary design alters Inter- to Trans-granular Fracture in AlCrN Thin Films. (15th September 2022) - Meindlhumer, M.; Ziegelwanger, T.; Zalesak, J.; Hans, M.; Löfler, L.; Spor, S.; Jäger, N.; Stark, A.; Hruby, H.; Daniel, R.; Holec, D.; Schneider, J.M.; et al.
Abstract: Despite their high hardness and indentation modulus, nanostructured crystalline ceramic thin films produced by physical vapour deposition usually lack sufficient fracture strength and toughness. This brittleness is often caused by underdense columnar grain boundaries of low cohesive energy, which serve as preferential paths for crack propagation. In this study, mechanical and structural properties of arc-evaporated Al0.9 Cr0.1 N thin films were analyzed using micromechanical tests, electron microscopy, atom probe tomography and in situ high-energy high-temperature grazing incidence transmission X-ray diffraction. Vacuum annealing at 1100°C resulted in the formation of regularly-distributed globular cubic Cr(Al)N and elongated cubic CrN precipitates at intracrystalline Cr-enriched sublayers and at columnar grain boundaries with sizes of ∼5 and ∼30 nm, respectively. Consequently, in situ micromechanical testing before and after the heat treatment revealed simultaneous enhancement of Young's modulus, fracture stress and fracture toughness by ∼35, 60 and 10%, respectively. The annealing-induced concomitant improvement of toughness and strength was inferred to precipitations observed within grains as well as at grain boundaries enhancing the cohesive energy of the grain boundaries and thereby altering the crack propagation pathway from inter- to transcrystalline. The here reported experimental data unveil the hitherto untapped potential of precipitation-based grain boundary design for the improvement of mechanical properties of transition metal nitride thin films. Graphical abstract: Image, graphical abstract